Minimizing Antioxidant Damage of Purple Sweet Potato var Antin 3 in Vacuum Packaging - Hasan, Abd. Azis; Hidayat, Nur; Kumalaningsih, Sri (Graduate School, Universitas Brawijaya, 2015)
The aim of this research is to find out the best immersion time in liquid nitrogen and the thickness of the packaging plastic to minimize the antioxidant damage of purple sweet potato during storage process. This research is conducted by using a factorial experiment in a randomized block design with two factors. In this research, first factor is the immersion time (0; 50; 60; 70 seconds), the second factor is the thickness of plastic (0.07 and 0.10 mm). The result of this research showed that the best immersion time is 70 seconds, while the best plastic thickness is 0.1 mm. The interaction of these two factors is the most effective to prevent antioxidants damage of purple sweet potato chips during 1 month storage.Keywords: antin 3, antioxidants, multilayer, vacuum packaging